Seed germination ecology of Conyza sumatrensis populations stemming from different habitats and implications for management - Xu, Yanyun; Ye, Junyong; Khalofah, Ahlam; Tan, Ali Kee Zuan; Ullah, Rehmat; El-Shehawi, Ahmed M. (Public Library of Science, 2021)
Conyza sumatrensis (Retz.) E. H. Walker is an obnoxious weed, emerging as an invasive species globally. Seed germination biology of four populations of the species stemming from arid, semi-arid, temperate, and humid regions was determined in this study. Seed germination was recorded under six different environmental cues (i.e., light/dark periods, constant and alternating day and night temperatures, pH, salinity, and osmotic potential levels) in separate experiment for each cue. Populations were main factor, whereas levels of each environmental cue were considered as sub-factor. The impact of seed burial depths on seedling emergence was inferred in a greenhouse pot experiment. Seed germination was recorded daily and four germination indices, i.e., seed germination percentage, mean germination time, time to reach 50% germination, and mean daily germination were computed. Tested populations and levels of different environmental cues had significant impact on various seed germination indices. Overall, seeds stemming from arid and semi-arid regions had higher seed germination potential under stressful and benign environmental conditions compared to temperate and humid populations. Seed of all populations required a definite light period for germination and 12 hours alternating light and dark period resulted in the highest seed germination. Seed germination of all populations occurred under 5–30°C constant and all tested alternate day and night temperatures. However, the highest seed germination was recorded under 20°C. Seeds of arid and semi-arid populations exhibited higher germination under increased temperature, salinity and osmotic potential levels indicating that maternal environment strongly affected germination traits of the tested populations. The highest seed germination of the tested populations was noted under neutral pH, while higher and lower pH than neutral had negative impact on seed germination. Arid and semi-arid populations exhibited higher seed germination under increased pH compared to temperate and humid populations. Seed burial depth had a significant effect on the seedling emergence of all tested populations. An initial increase was noted in seedling emergence percentage with increasing soil depth. However, a steep decline was recorded after 2 cm seed burial depth. These results indicate that maternal environment strongly mediates germination traits of different populations. Lower emergence from >4 cm seed burial depth warrants that deep burial of seeds and subsequent zero or minimum soil disturbance could aid the management of the species in agricultural habitats. However, management strategies should be developed for other habitats to halt the spread of the species.